Prediction and measurement of diuretic responsiveness after oral administration of furosemide to healthy dogs and dogs with congestive heart failure. (30th October 2020) - Loughran, Kerry A.; Larouche‐Lebel, Éva; Huh, Terry; Testani, Jeffrey M.; Rao, Veena S.; Oyama, Mark A.
Abstract: Background: In human patients, cumulative urine volume (uVol) and urine sodium (uNa) can be predicted using spot urine samples and these quantitative measures help detect low diuretic responsiveness (LDR). Hypothesis/objectives: Formulas using spot urine samples predict cumulative uVol and uNa output after oral administration of furosemide to dogs. Animals: Eight healthy dogs, 6 dogs with congestive heart failure (CHF). Methods: Prospective interventional study. Spot urine samples at 180 and 270 minutes after furosemide (3 mg/kg PO) were used to predict cumulative uVol and uNa output over 7 hours. Differentiation of dogs fulfilling predefined criteria for LDR was examined using receiver operating characteristic (ROC) curves. Results: Predicted uNa output at 180 minutes ( r s = 0.763, [95% confidence interval [CI], 0.375‐0.923], P = .002) and 270 minutes ( r = 0.816, [95% CI, 0.503‐0.940], P < .001) was highly correlated to 7‐hour uNa output. Predicted uVol at 180 minutes ( r = 0.598, [95% CI, 0.098‐0.857], P = .02) and 270 minutes ( r = 0.791, [95% CI, 0.450‐0.931], P < .001) was moderately correlated to 7‐hour uVol. Predicted uNa using 180‐minute (area under the curve [AUC], 0.933 [95% CI, 0.804‐1.000]) and 270‐minute (AUC, 0.911 [95% CI, 0.756‐1.000]) samples identified dogs with LDR (n = 5) with high accuracy. Conclusions and Clinical Importance: Urinary Na excretion and uVol are complementary but distinct aspects of diuretic responsiveness in dogs. Quantification of diuretic responsiveness in the clinical setting opens new diagnostic, treatment, and monitoring strategies.